ANALISIS PERTUMBUHAN EKONOMI SEKTOR PRIMER DI PROPINSI SUMATERA SELATAN - Nurul Huda; Taufiq Marwa; Muhammad Syirod Soleh (Jurnal Ekonomi Pembangunan, 2007)
The title of this research is â€œEconomics Growth Analysis of Primary Sector in South of Sumatera Provinceâ€. This research was conducted to explain the effect of credit distribution, labor and development expenditure toward the economics primary sector growth in South of Sumatera Province. This research coped with South of Sumatera Province. The writers used secondary data periode 1991 to 2005 in this research. The method in this research is distributed lag-model to find the significant hypothesis about the infuence of credit distribution, labor and development expenditure toward the economics primary sector growth in South of Sumatera Province. Based on the result of the analysis, it showed that the credit distribution, labor and development expenditure toward the economics agricultural sector growth in South of Sumatera Province has a significant effect. On the other hands, the credit distribution and development expenditure toward the economics mining sector growth in South of Sumatera Province does not have a significant effect. In conclusion, the result showed that there was a significant effect on credit distribution, labor and development expenditure toward the economics primary sector growth in South of Sumatera Province. Keywords: Economic Growth, Primary Sector, Credit Distribution, Labor